FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PROLL TAPE PADA UD. PRIMADONA JEMBER - Shanti Maulina Ningrum; Ratih Puspitorini Y. A.; Wenny Dhamayanthi (Jurnal Ilmiah Inovasi, 2015)
This research title is Factors - Factors Affecting Purchase DecisionÂ  Proll Tape in UD. Primadona Jember .The purpose of this research is to analyze and test the effect of independent variables simultaneously, partially and the variables that affect the dominant on purchasing decisions proll tape. This study took a sample of 40 respondents. Data were analyzed using statistical software SPSS version 16 with multiple linear regression model. Before analyzing the multiple linear regression to tested the validity and reliability. The results of the research conducted showed that regression testing F test showed that all independent variables have a significant effect on purchasing decisions. Regression testing test showed that the independent variables that affect the purchasing decisions of the variable packaging. While independent variables were not significant effect of variable price and taste. Dominant variable in affecting purchasing decisions in UD. Primadona is variable packaging.